The relationship of the teaching competencies of the primary school teacher with the development of social responsibility for the fifth-year primary learners - MEKTOUT , Amar; KETFI , Azouz (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2023)
The current study mainly aimed to evaluate the nature of the relationship between the teaching competencies of the teacher and the development of social responsibility among fifth-year primary school students, based on the assumption that the teaching competencies of the teacher have a strong correlation with the development of social responsibility for the students. This study was conducted within a geographical scope that included 5 learners. cohorts at Alshahid Hadibi Farhat primary School in Sidi Ameur, M'Sila Province. After the researcher controlled his sample consisting of 153 learners and 5 teachers specializing in the Arabic language, and relying on a number of tools, the most important of which were the teaching competencies scale and the learner's social responsibility scale, using the descriptive approach, the researcher came up with a set of partial results: -There is a strong positive linear relationship between the teacher's planning competencies and the development of social responsibility among fifth- year primary school students. -There is a strong positive linear relationship between the teacher's implementation competencies and the development of social responsibility among fifth- year primary school students. -There is a strong positive linear relationship between the teacher's evaluation competencies and the development of social responsibility among fifth- year primary school students. Accordingly, the main result that was confirmed to him was: There is a strong, positive linear relationship between the teaching competencies of the teacher and the development of social responsibility among fifth-year primary school students. The responses of the sample members showed that: The more the teacher plans his lesson well and contains values that help build the learner’s personality, and the more the implementation is consistent with what was stated in the planning and is consistent with positive interaction within the classroom, and the more the teacher accurately evaluates the steps of planning and implementation and the behavior of his learners even outside the classroom, the more social responsibility will be develop among the students.